2015
DOI: 10.1186/s12889-015-2401-2
|View full text |Cite
|
Sign up to set email alerts
|

Translating a heart disease lifestyle intervention into the community: the South Asian Heart Lifestyle Intervention (SAHELI) study; a randomized control trial

Abstract: BackgroundSouth Asians (Asian Indians and Pakistanis) are the second fastest growing ethnic group in the United States (U.S.) and have an increased risk of atherosclerotic cardiovascular disease (ASCVD). This pilot study evaluated a culturally-salient, community-based healthy lifestyle intervention to reduce ASCVD risk among South Asians.MethodsThrough an academic-community partnership, medically underserved South Asian immigrants at risk for ASCVD were randomized into the South Asian Heart Lifestyle Intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 54 publications
3
107
1
1
Order By: Relevance
“…The study team conducted FGDs to obtain a broad range of community beliefs 6 about lifestyle behaviours among South Asian Americans. FGDs were stratified by sex and age (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) or 40+ years) to create homogeneous groups of participants, minimise hierarchy development that may reduce data quality and enable structured analytical comparisons. 6 Trained moderators, matched to participants' sex, used a semistructured interview guide to elicit conversation around lifestyle behaviours, barriers and motivators for exercise and healthy eating, and feedback on possible programme components.…”
Section: Formative Qualitative Researchmentioning
confidence: 99%
“…The study team conducted FGDs to obtain a broad range of community beliefs 6 about lifestyle behaviours among South Asian Americans. FGDs were stratified by sex and age (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) or 40+ years) to create homogeneous groups of participants, minimise hierarchy development that may reduce data quality and enable structured analytical comparisons. 6 Trained moderators, matched to participants' sex, used a semistructured interview guide to elicit conversation around lifestyle behaviours, barriers and motivators for exercise and healthy eating, and feedback on possible programme components.…”
Section: Formative Qualitative Researchmentioning
confidence: 99%
“…Knowledge on unhealthy behavior pattern of people with metabolic syndrome is considered crucial for creating a tailored lifestyle intervention program and a tailored regimen might help patients with metabolic syndrome to be motivated to change unhealthy behaviors [11,12]. The purpose of this study was to investigate the clustering pattern of four major lifestyle risk factors—smoking, heavy drinking, poor diet, and physical inactivity—among people with metabolic syndrome in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…SAHELI intervention was designed utilizing the intervention model (Figure 1). Although SAHELI did not show a difference in physical activity or saturated fat intake, which were the primary outcomes, between the intervention and control group, the results did find a significantly greater reduction in weight (−1.5 kg) and hemoglobin A1c (−0.43%) (Kandula et al, 2015), which are the two identified intermediate CVD risk factors (Figure 1). Through this process evaluation, participant burden was identified as a deterrent in ensuring accurate dietary recall and in maintaining continuity of intervention through telephone counseling.…”
Section: Discussionmentioning
confidence: 95%